Synergizing Early Childhood Education Management and Higher Education: A Path to Enhanced Business Sustainability - Ahmad Nur Budi Utama; Agus Syarif; Bunga Ayu Wulandari; Romi Kurniadi (STAI Hubbulwathan Duri, 2024)
Early Childhood Education (ECE) in Indonesia faces critical challenges, including limited financial resources, inadequate managerial support, and weak marketing strategies, which hinder the sustainable growth of ECE institutions. This study proposes a collaborative business management model between ECE institutions and universities to address these issues. The research employed a Focus Group Discussion (FGD) approach, involving 15 participants comprising ECE managers and university representatives. Discussions centered on operational challenges faced by ECE institutions and the potential for universities, leveraging their expertise in business, research, and student engagement, to provide strategic managerial and financial support. Data were analyzed using thematic analysis to design a collaborative model. The findings revealed that universities can play a pivotal role in addressing ECE management constraints by offering expertise in marketing strategies, financial planning, and operational management. The proposed model emphasizes mutual benefits, with universities enhancing their community engagement and Key Performance Indicators (KPIs), while ECE institutions receive essential support to improve educational quality and sustainability. This study addresses a gap in the literature by demonstrating the feasibility and advantages of university-ECE partnerships. Such collaborations can transform both sectors by fostering cross-sector policies, improving community development, and enhancing educational outcomes. The collaborative model offers a strategic solution to ECE sustainability challenges in Indonesia. Future efforts should focus on policy frameworks to support these partnerships, enabling broader implementation and long-term impact on educational and societal advancement.